ANALISIS LOGAM BERAT PADA SEDIAAN EYE SHADOW BENTUK CAKE YANG BEREDAR DI ONLINE SHOP SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Pujianto, Dina Lisdiana; Supriyadi, Supriyadi; Rejeki, Endang Sri (Jurnal Farmasi & Sains Indonesia, 2024)
Eye shadow is an eyelid makeup that is used to make the eyes appear darker so that the eyelids look more sunken in. Heavy metals are generally impurities in the basic ingredients of cosmetics that arise during production. The purpose of the study was to determine the levels of heavy metals in eye shadow in accordance with BPOM RI No. 12 Tahun 2019. This study used purposive sampling method. Sample preparation was carried out using the dry deconstruction method. The study began with qualitative analysis indicated by the appearance of heavy metal absorbance in reading with a selective cathode lamp in atomic absorption spectrophotometry (SSA). Determination of heavy metal levels using atomic absorption spectrophotometry (SSA) at a wavelength of 197.3 nm for arsenic, 228.8 nm for cadmium, and 283.3 nm for lead. The results of heavy metal levels were then analysed using SPSS 26.0 one-sample T-tests. The results showed that all samples A, B, C, D, and E were positive for arsenic, cadmium, and lead with respective levels ranging from 0.19227-0.81752 mg/kg; 0.37014-1.05215 mg/kg; and 1.44905-6.22936 mg/kg. The results obtained still meet the BPOM contamination limits, which are < 5 mg/kg for arsenic, < 5 mg/kg for cadmium, and < 20 mg/kg for lead, thus all samples are still within safe limits in accordance with the requirements of BPOM RI No. 12 Tahun 2019.